Muscle fatigue increases metabolic costs of ergometer cycling without changing VO2 slow component - Ratkevicius, A.; Stasiulis, A.; Dubininkaite, L.; Skurvydas, A. (Journal of Sports Science & Medicine, 2006)
The aim of the present study was to investigate effects of muscle fatigue on oxygen costs of ergometer cycling and slow component of pulmonary oxygen uptake (VO2) kinetics. Seven young men performed 100 drop jumps (drop height of 40 cm) with 20 s of rest after each jump. After the subsequent hour of rest, they cycled at 70, 105, 140 and 175 W, which corresponded to 29.6 ± 5.4, 39.4 ± 7.0, 50.8 ± 8.4 and 65.8 ± 11.8 % of VO2peak, respectively, for 6 min at each intensity with 4-min intervals of rest in between the exercise bouts. The VO2 response to cycling after the exercise (fatigue condition) was compared to ergometer cycling without prior exercise (control condition). From 3rd to 6th min of cycling at 105, 140 and 175 W, VO2 was higher (p < 0.05-0.01) when cycling in the fatigue compared to the control condition. Slow component of VO2 kinetics was observed when cycling at 175 W in the control condition (0.17 ± 0.09, l·min-1, mean ± SD), but tended to decrease in the fatigue condition (0.13 ± 0.15 l·min-1). In summary, results of the study are in agreement with the hypothesis that muscle fatigue increases oxygen costs of cycling exercise, but does not affect significantly the slow component of pulmonary oxygen uptake (VO2) kinetics.